Guía metodológica de inclusión educativa, dirigida al personal docente de la Unidad Educativa "Emaús" de Fe y Alegría, en la ciudad de Quito - Fuenmayor Aguayo, María Alexandra (2015)
This work is aimed at the compression of the theme of Inclusive Education. It is about "Methodological Guide Inclusive Education for teachers in the Fe y Alegría Educational Unit of Quito city". This one has a main objective, the development of guidelines to provide efficient services to students with Special Educational Needs, appropriate to their individual capacities, to the current educational system requirements and future demands of society and the world of work. It is therefore necessary that the ordinary general curriculum adapts these needs and the teaching and learning processes are regulated in content, objectives, evaluation, promotion and accreditation of these students. In this way, the guide aims to guide teachers in their teaching practice and most important in their classrooms, for in this way comply with the right of all people, which is the benefit from an adequate formation, develop their aptitudes and skills, and enable them to increase and facilitate their social inclusion.